Dating the Old Norse Poetic Edda a multifactorial analysis of linguistic features - Sapp, Christopher D. (Studies in Germanic linguistics,, 2022)
"This book offers new dating of the poems of the Old Norse Poetic Edda, perhaps our best sources about the mythology and legends of the Viking Age. This study compares the anonymous Eddic poems to dated skaldic poems with respect to five phenomena that develop diachronically in early Old Norse: the expletive particle of, types of negation, word order, types of relative clause, and metrical criteria. After examining these dating features individually, the three most reliable criteria-the particle of, negation, and relative clause type-are combined into a multifactorial analysis using a Naïve Bayes Classifier. The classifier assigns a date to each Eddic poem, and these proposed dates have interesting implications for our understanding of these texts as sources for the medieval history, mythology, linguistics, and literature of the Germanic peoples. This book will have broad interdisciplinary interest, not just to historical linguists and philologists but also to scholars of Norse history, literature, and mythology"--